Effects of Curing Period of Livestock Droppings on the Growth and Yield of Okra (Abelmoschus esculentus L.) Varieties - S. Y. Abdulmaliq; Y. A. Abayomi; M. O. Aduloju; O. Olugbemi (International Journal of Agronomy)
A field study was carried out across two cropping seasons (2010 and 2011) to explore the effects of curing periods of cow dung and poultry droppings used in soil amendment on the performance of two okra (Abelmoschus esculentus L.) varieties: NHAe 47-3 and LD 88-1. The effects of cow dung and poultry droppings cured for 3, 6, and 9 weeks were compared to that of NPK fertilizer (100 kg N ha−1 and 60 kg ha−1 each of P2O5 and K2O) and a control (no amendment). The application of organic amendment cured for 3 to 6 weeks enhanced the growth and yield of okra when compared with inorganic fertilizer or the unamended soil across the two cropping seasons. Based on this outcome, the use of adequate quantity of livestock droppings cured for 3–6 weeks, in case of poultry dropping, and for 6 weeks, in case of cow dung, is recommended as an alternative to inorganic fertilizer. The variety NHAe 47-4 was also demonstrated to give better yield (1.73 and 2.18 t ha−1) than LD 88-1 (1.63 and 1.80 t ha−1) in the years 2010 and 2011, respectively.